A phase‐shift‐free synchronous reference frame filter‐based position sensorless control method for open‐winding permanent magnet generator system - Wenjuan Hao (IET Electric Power Applications, 2021)
Abstract An open‐winding permanent magnet generator (OWPMG) system that offers features like fewer switching devices and high integration can be used in multi‐input generator systems. To achieve high‐accuracy position sensorless operation for the OWPMG system, this study investigates a phase‐shift‐free synchronous reference frame filter (SRFF‐PSF) for use in the sliding mode observer (SMO) position sensorless algorithm. The proposed SRFF‐PSF can completely restore the fundamental component of back‐electromotive force (EMF) without phase shift and filter out the high‐order harmonics owing to the following two improvements. First, the fundamental phase lag is eliminated by removing the low‐pass filter between the back‐EMF and the SRFF. Second, the error iteration of the output position angle is avoided by using the synchronous angle information from an additional phase locked loop module for the coordinate transformation of the SRFF. Based on the aforementioned improvements, the proposed method can effectively solve the phase shift problem in position estimation. The correctness and effectiveness of the method are verified by the experimental results.